Molecular evidence of the reservoir competence of water buffalo (Bubalus bubalis) for Anaplasma marginale in Cuba - Obregon, Dasiel; Corona, Belkis G.; la Fuente, Jose de; Cabezas-Cruz, Alejandro; Goncalves, Luiz Ricardo [UNESP]; Matos, Carlos Antonio [UNESP]; Armas, Yasmani; Hinojosa, Yoandri; Alfonso, Pastor; Oliveira, Marcia C. S.; Machado, Rosangela Z. [UNESP] (Elsevier B.V., 2018)
Water buffalo (Bubalus bubalis) is a potential reservoir for Anaplasma marginale in livestock ecosystems of tropical countries. However, their participation in the epidemiological process of bovine anaplasmosis in endemic areas remains unclear. In the present study, the reservoir competence of water buffalo for A. marginale was explored by focusing on the analysis of rickettsemia levels in carrier animals, and the genetic characterization of A. marginale strains from cattle and buffalo. Eight groups of cattle and water buffaloes were randomly selected from cohabiting herds in four livestock ecosystems of Cuba, together with two control groups from unrelated cattle and buffalo herds. A total of 180 adult animals (88 water buffalo and 92 cattle) were sampled. Rickettsemia in carrier animals was determined by quantitative real-time PCR. The rickettsemia (parasitemia) levels in cattle were higher than in buffaloes, however the rickettsemia in buffalo may be enough to infect R. microplus ticks. The genetic diversity of A. marginale was assessed by strain characterization and phylogenetic analysis of 27 mspl a gene sequences. The results showed genetic similarity among strains from cattle and water buffalo, suggesting the occurrence of cross-species transmission.
Keywords: Water buffalo; Cattle; A. marginale; Rickettsemia; Genetic diversity; Cross-transmission